2008
DOI: 10.1007/s11239-008-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a clinical decision support system to identify heparin induced thrombocytopenia

Abstract: BACKGROUND: Subtle decreases in platelet count may impede timely recognition of heparin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Criticisms of the decision analysis included the use of bleeding estimates based on doses of argatroban that are no longer used, delay in obtaining prompt results even at centers that have the SRA or HIPA available, and the potential for harm in missing cases of HIT for HIT antibodies in patients who became thrombocytopenic (5%-19%), and a low rate of initiation of a nonheparin anticoagulant when the suspicion of HIT was high enough to warrant laboratory testing (0%-55%). [73][74][75] The fi ndings of the above studies suggest previous recommendations for platelet monitoring have not been widely implemented. 76 Furthermore, when platelet count monitoring is done and platelets drop, heparin is not necessarily stopped nor is a nonheparin anticoagulant started.…”
Section: Commercially Available Elisa Using Manufacturer's Optical Dementioning
confidence: 99%
“…Criticisms of the decision analysis included the use of bleeding estimates based on doses of argatroban that are no longer used, delay in obtaining prompt results even at centers that have the SRA or HIPA available, and the potential for harm in missing cases of HIT for HIT antibodies in patients who became thrombocytopenic (5%-19%), and a low rate of initiation of a nonheparin anticoagulant when the suspicion of HIT was high enough to warrant laboratory testing (0%-55%). [73][74][75] The fi ndings of the above studies suggest previous recommendations for platelet monitoring have not been widely implemented. 76 Furthermore, when platelet count monitoring is done and platelets drop, heparin is not necessarily stopped nor is a nonheparin anticoagulant started.…”
Section: Commercially Available Elisa Using Manufacturer's Optical Dementioning
confidence: 99%
“…4 However, adherence to platelet count monitoring, testing for HIT antibodies if thrombocytopenia develops, and switching to HIT-safe anticoagulation when HIT is suspected is challenging, resource intensive, and may not reduce the adverse consequences of HIT. 6,9,[28][29][30] Previous studies have demonstrated that more than half the thrombotic events in HIT occur after the cessation of heparin without additional treatment of HIT. 8,11 In our study, we observed that more than half the HITT cases (17 of 31) had the thromboembolic event diagnosed after the diagnosis of HIT and while they were receiving HIT-safe anticoagulation, which emphasizes not only the need for early recognition and treatment but also the need to prevent HIT.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The type and delivery of the CDSS may influence the results. Effective decision support combines information with specific mandated tasks.…”
Section: Discussionmentioning
confidence: 99%